2003
DOI: 10.1152/physrev.00008.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Hibernation: Cellular and Molecular Responses to Depressed Metabolism and Low Temperature

Abstract: Mammalian hibernators undergo a remarkable phenotypic switch that involves profound changes in physiology, morphology, and behavior in response to periods of unfavorable environmental conditions. The ability to hibernate is found throughout the class Mammalia and appears to involve differential expression of genes common to all mammals, rather than the induction of novel gene products unique to the hibernating state. The hibernation season is characterized by extended bouts of torpor, during which minimal body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
971
3
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 997 publications
(1,013 citation statements)
references
References 255 publications
(342 reference statements)
29
971
3
10
Order By: Relevance
“…Several authors (e.g. Hermes-Lima and Zenteno-Sav铆n 2002; Carey et al 2003) have suggested that this cellular resistance is mediated in part by the upregulation of antioxidant enzymes, possibly to ameliorate macromolecular damage from ROS production during arousal from torpor. We tested the hypothesis that the African lungWsh P. dolloi adaptively enhances antioxidant capacity during estivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors (e.g. Hermes-Lima and Zenteno-Sav铆n 2002; Carey et al 2003) have suggested that this cellular resistance is mediated in part by the upregulation of antioxidant enzymes, possibly to ameliorate macromolecular damage from ROS production during arousal from torpor. We tested the hypothesis that the African lungWsh P. dolloi adaptively enhances antioxidant capacity during estivation.…”
Section: Discussionmentioning
confidence: 99%
“…Hermes-Lima and Zenteno-Sav铆n 2002; Carey et al 2003) have suggested that upregulation of intracellular antioxidant enzymes during estivation and hibernation protects against stress-related cellular injury. Indeed, there is some evidence for this in estivating pulmonate land snails (Hermes-Lima and Storey 1995;RamosVasconcelos and Hermes-Lima 2003).…”
mentioning
confidence: 99%
“…This hypothetical scenario is reasonable at a storage temperature of 24 掳C, with Bag 1 suppressing cell death. At a storage temperature of 4 掳C, however, Bag 1 appears to undergo a profound metabolic depression reminiscent of a torpor state for reducing energy costs (Carey et al, 2003). Regardless, our data provide ex vivo evidence for a crucial role of temperature in Bag 1 kinetics.…”
Section: Discussionmentioning
confidence: 62%
“…Many genes are differentially regulated between summer and winter in hibernators, and many proteins undergo post-translational modifications (Carey et al, 2003;Lee et al, 2006). These differentially expressed genes include 伪 2 -macroglobulin (Srere et al, 1995), the H3 histamine receptor (Sallmen et al, 2003), TBG (thyroxine binding globulin) (Epperson and Martin, 2002), and the 'early-intermediate' genes such as c-fos and c-jun (O'Hara et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that hibernators are widespread among the Mammalia (Carey et al, 2003), the study of mammalian hibernation in the past has not benefited from the availability of defined mutants, stock centers, or sequenced genomes. Low coverage genome sequencing has only recently begun on three distantly related hibernating mammals: the little brown bat (Myotis lucifugus), European hedgehog (Erinaceus europaeus), and thirteen-lined ground squirrel (Spermophilus tridecemlineatus).…”
Section: Introductionmentioning
confidence: 99%